A Fast Harmonic Detection Method Based on Recursive DFT - Xin Limin; Xu Weisheng; Yu Youling (2007 8th International Conference on Electronic Measurement and Instruments, 2007)
This paper proposed a fast harmonic detection method based on recursive discrete Fourier transform, which is suitable for real-time calculation. The main features of the proposed method are that (1) it can be used to detect only specific harmonic components, (2) the recursive method needs few calculation, so harmonic detection and compensation can be implemented on-line, (3) spectrum update is implemented in a step larger than one sampling period to avoid over-sampling, (4) time-domain windowing has been taken into account to reduce spectral leakage caused by asynchronous sampling. These characteristics make the proposed method especially compatible with hybrid active filter, in which structure only specific harmonic components concerned are needed to be analyzed and harmonic compensation is implemented almost immediately.